Transfection of an Fc gamma receptor cDNA induces T cells to become phagocytic. - Hunter, S (1994)
The human receptor Fc gamma RIIA for the Fc portion of IgG (Fc gamma) was expressed in a human T-cell line and conferred on these cells the ability to perform IgG antibody-stimulated phagocytosis. Crosslinking Fc gamma RIIA with anti-Fc gamma RII monoclonal antibody also induced tyrosine phosphorylation of multiple proteins including Fc gamma RIIA, ZAP-70, p72SYK, and phospholipase C gamma 1 subunit and an increase in intracellular Ca2+ concentration. The T cell receptor-associated zeta-chain was not tyrosine-phosphorylated after crosslinking of Fc gamma RIIA, suggesting that the Fc gamma RIIA-mediated signals were independent of CD3. Fc gamma RIIA-mediated signal transduction was defective in a transfected mutant T-cell line exhibiting reduced expression of the tyrosine kinases LCK and FYN. These studies indicate that certain T cells can assume phagocytic properties after transfection of cDNA encoding an Fc gamma receptor with the capability of inducing a phagocytic signal.